Development of the Mersing tourism operator system for diver management in Mersing, Johor, Malaysia / Isma Ishak - Ishak, Isma (Faculty of Information Management, 2023)
The Mersing Tourism Operator System (MeTOS) is a comprehensive software solution developed to facilitate the efficient management of divers visiting the picturesque island of Mersing in Johor, Malaysia. Currently, all actions are recorded manually by hand in a book. Because humans make mistakes, this approach is very subjective and inconsistent. Based on the circumstance, a MeTOS was created. This research article presents an in-depth analysis of the development process, key features, and benefits of the MeTOS. The system aims to streamline diver management, enhance safety measures, and contribute to the sustainable growth of the local tourism industry. By offering real-time monitoring, data analytics, and communication tools, MeTOS empowers dive operators to provide a seamless and secure diving experience, ultimately promoting Mersing as a premier diving destination.